Comparison of the mechanical properties of low-cost bio fiber reinforced polymer composites - Ismael, Sanad Abdulkareem; Naeem, Samara Munaem (Zielona Góra: Uniwersytet Zielonogórski)
In this study, the physical, and mechanical properties of low-cost and biocomposites were evaluated. The walnut shell and date palm frond fibers were thermally treated in an oven at a temperature of 70 [degrees] C and then chemically treated with NaOH and distilled water solution, after these treatments, the biofiber materials were thermally treated again at 50[degrees]C.
Keywords: biocomposite; walnut shell; date palm fronds; tensile test; compression test